Evaluación agronómica de tres variedades de maní (arachis hypogaea l.) con diferente población en la zona de Quevedo - Vélez Arellano, Shirley Katherine (2011)
The research was conducted at the farm "Envy" owned by Mr. Joseph Aquilino Bazurto Velez, located at Km 20 road Quevedo - Babahoyo, whose geographical location is 01o 6 'height and 79th South 29' west longitude, was aimed at agronomic evaluation of three varieties of peanuts (Arachis hypogaea L.) with different people in the area of quevedo We used the design of randomized complete block design (RCBD) with 6 treatments and 4 repetitions, we evaluated the plant height at 15, 30, 45 and 60 days, days to flowering, flowers per plant, days harvest, number of pods per plant, number of grains per plant, yield in kg. In grain yield per plot and Kilogram per hectare. According to the results, it was observed that the height at 15 and 30 days showed no differences, but at 45 and 60 days if there were statistical differences The percentage of days to flowering showed statistical differences averaging at 40 days of treatment INIAP 381 T3 - T4 INIAP S1 381 - S2 380 INIAP Treatments T1 - T2 INIAP S1 380 - S2 by an average of 42 days and the highest value on days to flowering were for INIAP 382 T5 - T6 INIAP S1 382 - S2 at 45 days showed 100% of flowering plants. Regarding on toll plant pod on interaction treatments remain Statistically significant differs Best T5 INIAP Treatment 382 - S1 Rosita; with an average pods 38.00 plant. Regarding the number of grains per plant did not show statistical differences, with the largest values for the treatment T5 (INIAP 382 - Candy S1) with an average of 78.00 grains per plant and the T6 treatment (INIAP 382 - Candy S2) with a average of 58.75 grains per plant. With regard to plot grain yield (Kg) of the treatments showed statistical differences, the best treatment was the T5 (INIAP 382 - Candy S1) with an average of 5.53 kilograms in obtaining 12m2 per hectare yield of 4605.25 kilograms, the T6 (INIAP 382 - Candy S2) with an average of 4.92 kilograms in obtaining 12m2 per hectare yield of 4095.25 kilograms, followed by T2 (INIAP 380 - S2) to 4.42 kilograms in 12m2 and a yield per hectare of 3683.50 kilograms and T1 (INIAP 380 - S1) with 12m2 4.41 kilograms per hectare and a yield of 3671.50 kilograms and the results under T4 treatment (INIAP 381 - Rosita S2) with 4 , 12 Kilograms en12m2 and a yield of 3433.00 kilograms and T3 (INIAP 381 - Rosita S1) with 3.69 kilograms en12m2 and yield per hectare of 3075.00. The treatments showed the same total cost was $ 8.30; get the bigger the INIAP T5 - 382 S2 Caramel with a total revenue of $ 44.22, a net profit of $ 35.92 and benefit cost of $ 5.33.